Bound together : how traders, preachers, adventurers, and warriors shaped globalization - Chanda, Nayan (Yale University Press, 2007)
"In this book, Nayan Chanda follows the exploits of traders, preachers, adventurers, and warriors throughout history as they have shaped and reshaped the world. For Chanda, globalization is a process of ever-growing interconnectedness and interdependence that began thousands of years ago and continues to this day with increasing speed and ease. Chanda reviews and illustrates the economic and technological forces at play in globalization today and concludes with a discussion of how we can and should embrace an inevitably global world."--BOOK JACKET.